2011
DOI: 10.4081/xeno.2011.e5
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid-induced glutathione status in tomato crop and resistance to root-knot nematode, Meloidogyne incognita (Kofoid & White) Chitwood

Abstract: Salicylic acid-(SA) is a plant defense stimulator. Exogenous application of SA might influence the status of glutathione-(GSH). GSH activates and SA alters the expression of defense genes to modulate plant resistance against pathogens. The fate of GSH in a crop following SA treatment is largely unknown. The SA-induced profiles of free reduced-, free oxidized-(GSSG) and protein bound-(PSSG) glutathione in tomato crop following foliar treatment of transplant at 5.0-10.0 μg mL -1 were measured by liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Maximum reduction in root infection and soil population was observed in BTH followed by SA and NA treatments. The results on reduction of root infection by M. incognita and nematode reproduction parallel those reported recently by Nandi et al (2003), Molinari and Baser (2010) and Meher et al (2011).…”
Section: Crop Incompatibility To M Incognitasupporting
confidence: 88%
See 1 more Smart Citation
“…Maximum reduction in root infection and soil population was observed in BTH followed by SA and NA treatments. The results on reduction of root infection by M. incognita and nematode reproduction parallel those reported recently by Nandi et al (2003), Molinari and Baser (2010) and Meher et al (2011).…”
Section: Crop Incompatibility To M Incognitasupporting
confidence: 88%
“…The samples were processed and analyzed as per the reported protocol for GSH and GSSG (Meher et al 2011); and for SA, ASA, JA, and CGA (Meher et al 2012). In brief, the samples were immediately extracted in 20 mL mixture of methanol:water (2:1) containing 3 % perchloric acid, 0.1 % trifluoroacetic acid, 0.2 mM bathophenanthroline disulfonic acid, and 10 lg/mL methyl paraben.…”
Section: Sample Preparation and Liquid Chromatography (Lc)mentioning
confidence: 99%
“…Moreover, a number of studies have demonstrated that exogenous treatments with SA induce resistance to different pathogens in different species (Edgar et al, 2006;Mandal et al, 2009;Meher et al, 2011;Saikia et al, 2003;Shang et al, 2011;Spletzer and Enyedi, 1999;Wang and Liu, 2012). Studies with different plant-pathogen systems establishing a compatible, non-necrotizing interaction, have reported a significant accumulation of gentisic acid (GA) in infected plants (Bellés et al, 1999;Bellés et al, 2006;López-Gresa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nahG plants, which are unable to accumulate SA, are more susceptible to pathogens (Vlot et al, 2009). Several studies have demonstrated that exogenous treatments with SA induce resistance to different pathogens in tomato (Mandal et al, 2009;Meher et al, 2011;Shang et al, 2011;Spletzer and Enyedi, 1999) and other plant species (Edgar et al, 2006;Saikia et al, 2003;Wang and Liu, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently there are many approaches for controlling nematode using plant resistance inducing chemicals such as salicylic acid (SA) against nematodes (Ganguly et al, 1999;Molinari, 2006;Moslemi et al, 2016 andRadwan et al, 2017). Other reports mentioned that SA was promoted plant growth and decreased nematode infection by induction of plant resistance against root-knot nematode (Nandi et al, 2000;Molinari and Loffredo, 2006;Meher et al, 2011 andMostafanezhad et al, 2014b). Also, SA affected chemotaxis, motility, viability and hatching of Meloidogyne incognita in vitro (Wuyts et al, 2005).…”
mentioning
confidence: 99%